Beyond Food: using smart pest management in IoT greenhouses to foster environmental sustainability - Deepthi Palakurthy; Subhashini Katpally; Sai Vaishnavi Buddharaju; Gitali Polapalli; Mohammad Kahtan A.; Chandrashekar Rakesh; Nijhawan Ginni; Kalra Ravi (E3S Web of Conferences, 2024)
Higher yields and year-round crop cultivation are provided by greenhouse farming, but there are drawbacks as well, such as the need to maintain ideal environmental conditions and safeguard crops from pests. Conventional techniques frequently use chemical pesticides, which raises issues for the environment and human health. Through the integration of smart pest management within an Internet of Things (IoT)-powered greenhouse, the “IoT GREEN” project provides a sustainable solution. This creative system monitors important environmental variables including temperature, humidity, light, and soil moisture using wireless sensors and a Raspberry Pi. Farmers are given the ability to remotely monitor their crops thanks to the transmission of real-time data to an open-source cloud server and its visualization via a local web server. Importantly, “IoT GREEN” incorporates smart pest detection, which goes beyond simple monitoring. By identifying possible insect infestations early on and using sophisticated algorithms and picture recognition, this technology enables targeted interventions. “IoT GREEN” reduces dependency on hazardous pesticides by using non-chemical techniques like biocontrol agents or pheromone traps, promoting a more sustainable agricultural ecosystem. In addition to protecting crops, this all-encompassing strategy also fosters biodiversity, lowers environmental impact, and guarantees food safety.